Preparatory Strength Benchmarks for “Inverted Cross on Rings” in Male Elite and Junior Artistic Gymnasts - Christoph Schärer; Eddy Yusof; Claudio Capelli (Sports)
In men’s gymnastics, to build strength for static strength elements on rings (e.g., the Inverted Cross on Rings: ICR), general and ring-specific conditioning exercises are used. We aimed to examine the differences between elite and junior athletes in ring-specific strength in the ICR and the one-repetition maximum (1RM) in two conditioning exercises (Inverted Cross with Dumbbells: ICD; Seated Overhead Barbell Press: SOBP), to analyze the relationship between strength in the ICR and ICD and SOBP, and to establish preparatory strength benchmarks for ICR. Nine elite (20.97 ± 1.91 years, 66.01 ± 5.03 kg) and ten junior athletes (16.72 ± 0.55 years, 61.10 ± 7.9 kg) performed a maximum strength test for the ICR (five-second hold with pulley) and a 1RM test for the SOBP and ICD. Elite athletes were significantly stronger in the ICR and SOBP (22.36% and 33.2%; p < 0.001) but not in ICD (p = 0.13). Strong correlations (r > 0.65, p < 0.01) suggest that these exercises support strength development for the ICR. Although, the transfer into ring-specific strength must be trained separately, the benchmarks (SOBP: 150% body weight; ICD: 66%) offer coaches guidelines for optimizing training, prevent injury and promote physical resilience of elite athletes.